Mechanistic and Kinetic Investigations of ON/OFF (Photo)Switchable Binding of Carbon Monoxide by Chromium(0), Molybdenum(0) and Tungsten(0) Carbonyl Complexes with a Pyridyl‐Mesoionic Carbene Ligand. Issue 51 (1st September 2022) - Boden, Pit J.; Di Martino‐Fumo, Patrick; Bens, Tobias; Steiger, Sophie T.; Marhöfer, Daniel; Niedner‐Schatteburg, Gereon; Sarkar, Biprajit
Abstract: Invited for the cover of this issue are Gereon Niedner‐Schatteburg, Biprajit Sarkar and co‐worker at TU Kaiserslautern and the University of Stuttgart. The image depicts the selective dissociation of an axial CO from a metal complex. Read the full text of the article at 10.1002/chem.202201038 . Abstract : " Such high photochemical selectivity and efficient reversibility are known for only a limited number of carbonyl complexes ." This and more about the story behind the front cover can be found in the article at 10.1002/chem.202201038 ).